2005
DOI: 10.1602/neurorx.2.3.423
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic models of Alzheimer’s disease: Learning from animals

Abstract: Summary:As the scope of the problem of Alzheimer's disease (AD) grows due to an aging population, research into the devastating condition has taken on added urgency. Rare inherited forms of AD provide insight into the molecular pathways leading to degeneration and have made possible the development of transgenic animal models. Several of these models are based on the overexpression of amyloid precursor protein (APP), presenilins, or tau to cause production and accumulation of amyloid-␤ into plaques or hyperpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0
10

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(142 citation statements)
references
References 190 publications
(182 reference statements)
2
130
0
10
Order By: Relevance
“…Хорошо известно, что генетические/эпигенетические и средовые факторы являются триггерами событий, актуальных для патогенеза болезни Альцгеймера. Ис-следования, выполненные в течение 2-3 последних десятилетий, в основном были сосредоточены на изу-чении роли генетических факторов, что нашло свое отражение не только в идентификации новых генов-кандидатов, но и в создании трансгенных моделей бо-лезни Альцгеймера на животных [42]. Однако в течение последних 5-10 лет все большее внимание исследова-телей привлекает изучение действия факторов окружа-ющей среды на формирование хронического нейроде-генеративного процесса как в клинической практике, так и у животных с экспериментальными моделями бо-лезни Альцгеймера [43].…”
Section: влияние обогащенной среды на поврежденный мозг: возможности unclassified
“…Хорошо известно, что генетические/эпигенетические и средовые факторы являются триггерами событий, актуальных для патогенеза болезни Альцгеймера. Ис-следования, выполненные в течение 2-3 последних десятилетий, в основном были сосредоточены на изу-чении роли генетических факторов, что нашло свое отражение не только в идентификации новых генов-кандидатов, но и в создании трансгенных моделей бо-лезни Альцгеймера на животных [42]. Однако в течение последних 5-10 лет все большее внимание исследова-телей привлекает изучение действия факторов окружа-ющей среды на формирование хронического нейроде-генеративного процесса как в клинической практике, так и у животных с экспериментальными моделями бо-лезни Альцгеймера [43].…”
Section: влияние обогащенной среды на поврежденный мозг: возможности unclassified
“…49,50 These models recapitulate various aspects of AD and frontal temporal lobe dementia and are inherently useful for understanding the timing of neurogenetic changes in AD progression. Such studies have so far produced conflicting results showing increases, 51 non-significant changes, 52 and decreases 53 in hippocampal neurogenesis in mouse models that depend, in part, on methodological differences in markers for neurogenesis and the age of the animals.…”
Section: Future Directionsmentioning
confidence: 99%
“…In addition, although studies of knockout mice suggested that APP was not an essential protein [114], all the cleavage products of APP, including the large soluble N-terminus, Aβ and the C-terminus, have been shown to have physiological roles [28]. Thus, inhibition of β-or γ-secretase may interfere with physiological processes and cause significant adverse side effects [110,115].…”
Section: New Therapeutic Strategiesmentioning
confidence: 99%